Evaluation of universal newborn hearing screening in South African primary care - Katijah Khoza-Shangase; Shannon Harbinson (African Journal of Primary Health Care & Family Medicine, 2015)
Background: Universal Newborn Hearing Screening (UNHC) is the gold standard toward early hearing detection and intervention, hence the importance of its deliberation within the South African context.